Multitarget Compounds Designed for Alzheimer, Parkinson, and Huntington Neurodegeneration Diseases - Eleftheria-Emmanouela Katsoulaki; Dimitrios Dimopoulos; Dimitra Hadjipavlou-Litina (Pharmaceuticals, 2025)
Multitarget drugs are molecules with the ability to act simultaneously on different targets at the same time, and they have been evaluated in the last decade as a powerful tool in the development of promising therapeutics for neurodegenerative diseases. This is very useful for multifactorial diseases such as Alzheimer’s, Parkinson’s, and Huntington’s diseases, a group of neurological disorders that induce neurodegeneration and neuroinflammation. Successful drug design for multifactorial diseases depends on an interdisciplinary and collaborative approach. The complexity of the above pathologies has clearly demonstrated that such single-target drugs are inadequate to achieve a successful therapeutic result. Furthermore, molecules hitting more than one biological target exhibit also a safer profile. In this review, we present a comprehensive knowledge of recent research on multitarget synthetic approaches to confront Alzheimer’s, Parkinson’s, and Huntington’s neurodegenerative diseases.